An analysis of the achievement in physics of the secondary students of the Cagayan State University - Reyes, Nieves Ferrer (Animo Repository, 1983)
The study analyzed the achievement in physics of the secondary students of the Cagayan State University (CSU) of the school year 1982-1983. The sample for the study consisted of eighty-six (86) fourth year students. This is equivalent to twenty percent (20 percent) of the total fourth year secondary students of CSU. This sample further consisted of thirty (30) students from CSU-Piat, an agricultural school and fifty six (56) students from CSU-Tuguegarao, a trade school. An achievement test in Physics developed and validated by the Center for Educational Measurement (CEM) was used as the instrument. It is a fifty (50) multiple choice item test. It was administered to the respondents last February 1983 by the center. This same test was administered simultaneously to more than two thousand fourth year secondary students nationwide. This group of students served as the norm group of this study. Scoring of the test was computerized. Raw scores were transformed to standard scores by computer too, through the CEM testing center. The study aimed to answer the following problems: 1. What is the level of achievement in physics of the secondary fourth year students of the Cagayan State University? 2. Does the achievement in Physics of the respondents differ among the content areas? 3. Does the achievement in physics of the respondents differ between the knowledge-comprehension level and scientific process level? 4. Does the achievement in Physics of the agricultural students differ from those of the trade oriented students? 5. What are some of the misconceptions of the respondents based on their wrong answers to the achievement test? To answer these problems, the following data-analysis schemes are presented: 1. To describe the level of achievement in Physics of the respondents as a whole, the statistical data used were the mean percentage of correct responses, standard deviation and standard scores. The group of more than two-thousand students who took the test nationwide last February 1983 is used as the reference or norm group in describing the level of performance of the respondents. The mean percentage of correct responses of the norm group is fifty percent (50%). The norm group also had a standard score of 500 and a standard deviation of 100. 2. To test significant differences in the level of achievement in physics of the respondents as a whole among content areas (I,II,III and IV) and between the two cognitive levels (knowledge-comprehension and scientific processes levels), two-day analysis of variance (ANOVA) with repeated measures design was used. Two-way ANOVA computations were done by the Statistical Assistance for Reseatch (STAR) through Father Luke Moortgat, Ph.D. of the Statistical Center of De La Salle University. 3. To test significant differences in the levelof achievement in physics by content area and by cognitive level between the agricultural (CSU-Piat) students and the t-test trade (CSU-Tuguegarao) students, for independent samples was used. 4. To identify misconceptions based on the wrong answers on some items, responses were tallied by options. Items considered were those where frequency of the wrong option is lesser by five (5), equal to, or greater than the frequency of the right option. Among the wrong options, the misconception is the option with the highest frequency. The results of the data-analyses were as follows: 1. The respondents as a whole, had a mean percentage of correct response of forty percent (40%) . This means that on the average, the respondents answered correctly forty percent(40%) of the total fifty-item test. This is 10 units below the mean of the norm group which turned out to be fifty percent (50%). Thus, out of fifty items, the respondents on the average answered twenty-two (22) items correctly. The respondents, therefore, relatively performed below average of the norm group. 2. The respondents as a whole, had a standard score of 431. Since the norm group had a mean standard score of 500 and a standard deviation of 100, then the respondents were 0.69 below the mean of the norm group. This is, again, an indication that the CSU students performed relatively low. 3. There are significant differences in the respondents' achievement in Physics among the content areas. a. there is a significant differences in the mean standard scors of the following pairs of content area: a.1 Content Areas I and II. a.2 Content Areas I and III, a.3 Content Areas I and IV, a.4 Content Areas III and IV. b. There is no significant differences between the mean standard scores of the following pairs of content area: b.1 Content Areas II and III, b.2 Content Areas II and IV, The four coontent areas are as follows: Content I - Kinetics, Force and Motion, Gravitation, Content II - Energy, Properties of Matter, Structure of Matter, Content III - Water waves, Sound Waves, Light, Content IV - Electostatics, Electricity, Magnetism, Electromagnetism, Nuclear Energy 4. There is no significant differences in the achievement in physics of the respondents as a whole, between the two cognitive levels. The respondents significantly performed equally in both the scientific processes level and in the knowledge-comprehension level. 5. There is significant differences in the level of acheivement between the agricultural students and the trade students among the content areas. a. The trade students significantly performed better than the agriculture students in content areas I, II and III. b. There is no significant differences in the level of achievement between the agriculture and trade students in content area IV. 6. There is significant differences in the level of achievement between the agriculture and trade students in both cognitive levels. The trade students significantly performed better in both levels. 7. There were twenty-two (22) items considered with misconceptions. This, represents forty-four precent (44%) of the total fifty (50) items of the physics test. A finer analysis of the findings shows that the respondents did well on items dealing with energy and matter. However, they performed poorest on items dealing with sound waves, water waves and light. In the light of these findings, it is suggested that physics teachers should plan enrichment activities for the concept on energy and matter. However, they performed poorly on items dealing with sound waves, water waves and light. In the light of these findings, it is suggested that physics teachers should plan enrichment activities for the concepts on energy and matter. However, Content Area III, in terms of content, should be evaluated such that concepts included are these which are more relevant to vocational courses. If students find relevance of this content area to their course, perhaps their learning will be enhanced. Lesser time could be alloted to Content Area II to give more time for Content Area III: There are at least twenty-two (22) misconceptions based on wrong answers identified. Further analysis shows that the misconceptions identified were on items calling for quantitative relationship or interpretation, especially on graph or diagram interpretation. Thus, it is also suggested not only to physics teachers but also to mathematics teachers that physical quantities used in science classes be presented in the discussions of graphs, diagrams, and tables. Misconceptions based on wrong answers were identified but no further investigation was done to determine the factos explaining these misconceptions. This suggests a recommendation for future researches. Misconceptions identified should be placed by proper concepts. Further analysis of the results also indicated that the trade students significantly performed better than the agricultural students. This finding is contrary to the results found by the Bureau of Secondary Education (BSE). Contrary, because the Bureau found that the agricultural students significantly performed better than the trade students, although the subject tested were on English, Algebra and Science in general. But still, the findings of the Bureau is that agricultural students perform better in Mathematics and Science especially. In physics, the trade students did perform better. This findings calls for future researches to conduct similar study using other science subjexts like Biology and Chemistry.An analysis of the other varialbes explaining the difference in the achievement of the two groups is highly recommended too. Better yet, another set of vocational groups of students can be considered as repsondents. The number of respondents in this stud is quite limited, and so future efforts should consider a larger population and sample to make the findings more conclusive.